1997
DOI: 10.1159/000174149
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Basement Membrane Polyanionic Sites and Nitric Oxide in Genetically Salt-Sensitive and Resistant Hypertensive Rats

Abstract: Cationic colloid gold, a polycationic histochemical probe, was used to analyze the distribution of glomerular basement membrane (GBM) polyanions, including heparan sulfate protoglycan in genetic salt-sensitive (SBH/Y) and resistant (SBN/Y) hypertensive rats, with or without high dietary salt intake. GBM morphology, renal function and nitric oxide, as measured by plasma and urine nitrite (NO2) and nitrate (NO3) were also determined. In the salt-sensitive rats the high-salt dietary intake r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Salt loading, but not salt susceptibility per se, has been claimed to predispose the kidney to injury, for example, by rendering the kidneys more susceptible to angiotensin II-induced injury (16). We have previously shown in the Sabra rat that high salt intake is deleterious to the permselectivity of the glomerular basement membrane and that 1 mo of salt loading was sufficient to reduce the number of anionic sites in the lamina rara externa and interna (15). However, since we observed differential susceptibility to renal injury without salt loading in SBH/y and SBN/y, these mechanisms do not appear to play a role under these circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Salt loading, but not salt susceptibility per se, has been claimed to predispose the kidney to injury, for example, by rendering the kidneys more susceptible to angiotensin II-induced injury (16). We have previously shown in the Sabra rat that high salt intake is deleterious to the permselectivity of the glomerular basement membrane and that 1 mo of salt loading was sufficient to reduce the number of anionic sites in the lamina rara externa and interna (15). However, since we observed differential susceptibility to renal injury without salt loading in SBH/y and SBN/y, these mechanisms do not appear to play a role under these circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…We found a similar effect of salt loading in genetically hypertension salt-sensitive rats [24]and SHR [unpubl. data].…”
Section: Discussionmentioning
confidence: 71%
“…In a recent study [24]we found that chronic saline loading in rats is associated with similar alteration in the GBM functional size barrier. It may be hypothesized that saline loading in ADR nephropathy will result in a more severe GBM damage.…”
Section: Introductionmentioning
confidence: 70%